Risk factors for histological progression of non‐alcoholic steatohepatitis analyzed from repeated biopsy cases. Issue 8 (23rd January 2020) - Daijo, Kana; Nakahara, Takashi; Inagaki, Yuki; Nanba, Maiko; Nishida, Yuno; Uchikawa, Shinsuke; Kodama, Kenichiro; Oya, Kazuki; Morio, Kei; Fujino, Hatsue; Ono, Atsushi; Murakami, Eisuke; et al.
Abstract: Background and Aim: The most important prognostic factor for non‐alcoholic steatohepatitis (NASH) is liver fibrosis. The aim of this study is to examine clinical parameters involved in pathological progression in NASH patients who underwent repeated liver biopsy and to analyze the response to treatment with respect to NASH‐related single nucleotide polymorphisms (SNPs). We performed longitudinal analysis of genetic and clinical factors associated with progression of NASH. Methods: Eighty NASH patients who had undergone serial liver biopsies were enrolled in this retrospective cohort study. Histological exacerbation was determined based on non‐alcoholic fatty liver disease activity score (NAS) and liver fibrosis. Results: About 22.5% had progression of fibrosis, 22.5% had improvement of fibrosis, and 55.0% had no change. NAS increased in 12.5%, decreased in 61.3%, and remained stable in the remaining 26.3%. We examined factors associated with histological progression versus non‐progression. Poor response of alanine aminotransferase (ALT) levels, increase in HbA1c levels, and presence of the tumor necrosis factor risk allele in the rs1799964 SNP were identified as independent risk factors contributing to histological progression in NASH patients. In addition, we found that the histological progression rate varies with ALT response, HbA1c levels, and rs1799964 genotype. Conclusions: In this study, we clarified the serum ALT level and the clinical significance of HbA1c to evaluate the progression of fibrosis in Japanese NASH patients. Furthermore, the tumor necrosis factor SNP was more likely to be involved in the response than PNPLA3 SNP. By simultaneously evaluating three factors, it is possible to estimate the risk of histological progression more accurately.